Thymus transplantation - Markert, M. Louise; Devlin, Blythe H.; McCarthy, Elizabeth A. (Clinical immunology (Orlando, Fla.), 2010)
Thymus transplantation is a promising investigational therapy for infants born with no thymus. Because of the athymia, these infants lack T cell development and have a severe primary immunodeficiency. Although thymic hypoplasia or aplasia is characteristic of DiGeorge anomaly, in “complete” DiGeorge anomaly, there is no detectable thymus as determined by the absence of naive (CD45RA +, CD62L +) T cells. Transplantation of postnatal allogeneic cultured thymus tissue was performed in sixty subjects with complete DiGeorge anomaly who were under the age of 2 years. Recipient survival was over 70%. Naive T cells developed 3–5 months after transplantation. The graft recipients were able to discontinue antibiotic prophylaxis, and immunoglobulin replacement. Immunosuppression was used in a subset of subjects but was discontinued when naive T cells developed. The adverse events have been acceptable with thyroid disease being the most common. Research continues on mechanisms underlying immune reconstitution after thymus transplantation.